Effects of group hypnotic intervention on pregnant mental health and delivery mode: a retrospective analysis - Cui, Xuelian; Chen, Wei; Yuan, Xiaosong; Hu, Huiwen; Liu, Zhiwei (Frontiers in Medicine, 2025)
BackgroundDepression and anxiety are highly prevalent during pregnancy, with psychological interventions being recommended as the first-line treatment.ObjectiveThis study examined the effects of group hypnotic intervention on prenatal depression, anxiety symptoms, and delivery mode.MethodsIn a single-center retrospective observational design, 237 pregnant women were included. The intervention group received group hypnotic sessions, while the control group received standard prenatal care. Baseline sociodemographic and clinical characteristics were recorded, including scores on the Hospital Anxiety and Depression Scale (HADS), Hamilton Depression Rating Scale (HAMD), Hamilton Anxiety Rating Scale (HAMA), and heart rate variability (low-frequency/high-frequency ratio [LF/HF]). Measurements were collected at three gestational timepoints (pre-intervention, post-intervention, and 38 weeks’ gestation). Between-group and within-group differences in symptom scores and LF/HF were analyzed, and a logistic regression analysis assessed the association between the intervention and the delivery mode.ResultsWithin-group analyses demonstrated sustained improvement in depression/anxiety symptoms (p < 0.001) and increased LF/HF ratio (p < 0.001) in the intervention group from pre-intervention to 38 weeks’ gestation. In contrast, the control group exhibited reduced HADS, HAMD, and HAMA scores at post-intervention (vs. pre-intervention; p = 0.002–0.003), but returned to baseline levels at 38 weeks’ gestation (vs. pre-intervention, p = 0.083–0.216). Between-group comparisons revealed significantly greater reductions in HADS, HAMD, and HAMA scores across all time points in the intervention group vs. controls (p < 0.001 for all). Vaginal delivery rates were also significantly higher in the intervention group (p = 0.04).ConclusionGroup hypnotic intervention effectively alleviated prenatal depression and anxiety symptoms and improved vaginal delivery outcomes, suggesting its integration into routine prenatal mental healthcare protocols.